FINANCIAL REPORT ANALYSIS : Empirical Study of Aneka Tambang Tbk Company In 2023 - Mangasi Sinurat; Rico Nur Ilham; Mohd. Heikal (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This observation is to analyze the financial condition of a company, can be done by analyzing its financial statements. One way to find out the position of the company's financial condition in good condition is to conduct various analyzes, and one of them is ratio analysis. This savings aims to evaluate the financial performance of PT Aneka Tambang Tbk through financial ratio analysis. The method used for this analysis is descriptive analysis using liquidity ratio measurements, solvency, profitability, activity, and market. Research data and information are obtained from the Indonesia Stock Exchange. Every year, all ratios increase, namely current ratio, quick ratio, DAR, DER, GPM. NPM, ROA ROE, ITO, RTO, TATO, EPS, PER and DPR so that this company is said to have very good prospects and performance.